Geroprotection from ergothioneine treatment in Drosophila melanogaster by improving intestinal barrier and activation of intestinal autophagy - Hongyu Pan; Qianwang Zheng; Yuan Zou; Guozhao Luo; Mingzhen Tu; Na Wang; Jingru Zhong; Liqiong Guo; Junfang Lin (Food Science and Human Wellness)
Ergothioneine is a natural amino acid with powerful antioxidant activity. Previous studies have demonstrated that ergothioneine can increase the lifespan of Drosophila melanogaster and Caenorhabditis elegans, and enhance telomerase activity. In present study, the metagenomics sequencing and quantitative real-time polymerase chain reaction analysis were employed to characterize the composition and diversity of gut microbiome in aging flies. And the alterations in the gut barrier, gut morphology, and other gut physiological indicators of aging flies were evaluated. Here, the results showed that ergothioneine induced little variations in gut microbiota composition in flies at mid-life, and significant alterations in the gut microbiota populations were only observed in flies at late -life. And ergothioneine attenuated age-related gut injuries, including decreasing reactive oxygen species levels in intestinal enterocytes, reduction of intestinal cells death, and preservation of gut integrity in aging flies. Ergothioneine also improved the gut morphology by preserving the structure and shape of cell organelles and inducing the intestinal autophagy. And activation of intestinal autophagy also contributed to the longevity effect mediated by ergothioneine in an unidentified mechanism.